Bankruptcy of a Tourism Company: Money Back Mechanism in Russian Federation - KOZLOV, Dmitry Aleksandrovich (Journal of Environmental Management and Tourism, 2020)
The main aim of this paper is to analyze possible ways for tourists to return money in case of travel company’s bankruptcy. Russian Federation doesn’t have a civilized legal mechanism for real tourist’s protection. There are many government agencies, professional and public unions, laws etc., but in real life all of them can only declare the tourist’s rights. In fact, even the State itself can’t get money from a bankrupt travel company. According to key findings, on Russian travel market the money back situation is very complicated. The article proposes a mechanism for full money back. Practically, the only option is chargeback.